FUNGSI PENDIDIKAN ISLAM DALAM HIDUP DAN KEHIDUPAN MANUSIA - Arianti, ARIANTI (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2016)
Abstract: Education is a need in human life. It cannot be separated from the fact that the human has potention to educate and to be educated. Educaton has crucial role in the human life because it can form the intelligence, the personality, and the creativity of the students as human. For the reason, all componenets of education must be oriented to develop all the orientations. Shortly, education can be identified as an instrument to develop the basic potention in the human life that finally suppots them to play role as civilized creature. Kata Kunci: Fungsi Pendidikan dan Kehidupan Manusia